1990
DOI: 10.1016/0739-7240(90)90025-u
|View full text |Cite
|
Sign up to set email alerts
|

Opioid control of growth hormone in the suckled sow is primarily mediated through growth hormone releasing factor

Abstract: Endogenous opioid peptides mediate the effect of suckling on LH and PRL in the domestic pig. However, the role of opioids in modulating GH during lactation in swine is not known. Primiparous sows that had been immunized against GRF(1-29) conjugated to human serum albumin (GRF-HSA, n=5) or HSA (n=4) were used to determine changes in GH after naloxone. Treatments were imposed in all sows on day 21 of lactation when antibody titers were 9100 ± 1629. All sows received (LV.) naloxone (0.25 mgfkg) or saline (0.0125 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This observation is consistent with previous re ports in prepuberal heifers (21), cyclic (32) and lactating (33) cows, steers (34,35), lactat ing sows (36) and cyclic gilts (37).…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with previous re ports in prepuberal heifers (21), cyclic (32) and lactating (33) cows, steers (34,35), lactat ing sows (36) and cyclic gilts (37).…”
Section: Discussionsupporting
confidence: 93%
“…1 or 2. Other reports have demonstrated that naloxone decreased ST in the suckled rat (47) and pig (7). Naloxone was apparently present in sufficient quantities on day 47 (Exp.…”
Section: Discussionmentioning
confidence: 67%
“…Exogenous ST enhances retention of nitrogen (4), increases body weight gain in growing ruminants (1) and increases milk yield in dairy cows (3). During lactation in the pig and cow, suckling causes an increase in circulating prolactin and ST and a decrease in luteinizing hormone (LH,(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations